Hubungan Riwayat dalam Keluarga terhadap Kejadian Sindrom Down pada Anak dari Ibu yang Mengonsumsi Asam Folat Prenatal - Amanda Putri Gunarso (2023)
Down syndrome is a chromosomal disorder with the highest incidence. Down syndrome is a disorder caused by trisomy of chromosome 21. Based on the 2018 Riskesdas, the incidence of Down syndrome has increased by 0.08 percent from previous data. Family history is known to contribute to the mechanism of Down syndrome through inherited disorders. Down syndrome is one of the chromosomal abnormalities that contributes to the occurrence of congenital abnormalities. Folic acid plays an important role in embryonic and fetal development, particularly in DNA synthesis and in cell development and division. This study aims to determine the relationship between family history and the incidence of Down syndrome in children of mothers who consume prenatal folic acid. This type of research is observational analytic with a case control design with a research instrument in the form of a questionnaire. Data analysis used univariate and bivariate analysis using the chi square test on 34 case group respondents and 34 control group respondents. The case group consisted of mothers with children belonging to the Association of Parents of Children with Down Syndrome (POTADS) who consumed folic acid during pregnancy. The control group consisted of mothers of children in Cilandak Barat 08 Public Elementary School who took folic acid during pregnancy. The results showed that there was no significant relationship between family history and the incidence of Down syndrome in children of mothers who consumed prenatal folic acid (p=0.150).